2016
DOI: 10.1002/hon.2312
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐2 microglobulin as a significant prognostic factor and a new risk model for patients with diffuse large B‐cell lymphoma

Abstract: Previous reports have evaluated the prognostic value of serum beta-2 microglobulin (B2MG) level in patients with non-Hodgkin lymphoma. However, its role in predicting clinical outcome of patients with diffuse large B-cell lymphoma (DLBCL) in the rituximab era has not been extensively investigated. Here, we evaluated the prognostic value of B2MG and proposed a new prognostic model including B2MG for patients with DLBCL. A total of 274 patients with newly diagnosed de novo DLBCL were retrospectively analyzed. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 42 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…However, serum B2M levels also imply involvement of the immune reaction to the tumor because it is a component of major histocompatibility complex (MHC I) (49,50). Based on these grounds, several studies have shown the poor prognostic effect of serum B2M in DLBCL (30,51,52). However, these results are controversial, and most of these studies have shown difficulties in determining the universal optimal cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…However, serum B2M levels also imply involvement of the immune reaction to the tumor because it is a component of major histocompatibility complex (MHC I) (49,50). Based on these grounds, several studies have shown the poor prognostic effect of serum B2M in DLBCL (30,51,52). However, these results are controversial, and most of these studies have shown difficulties in determining the universal optimal cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of beta-2 microglobulin in patients with DLBCL treated with rituximab has not been fully investigated in previous studies except for the notable Japanese studies by Kanemsa et al and Miyashita et al [34, 35]. They reported that elevated serum beta-2 microglobulin was a poor prognostic predictor in patients with DLBCL in the rituximab era.…”
Section: Discussionmentioning
confidence: 99%
“…This elevated value is independently associated with unfavorable prognosis of most of the hematological malignancies (269, 273277). These associations persist despite adjustment for well-validated clinical prognostic scores and therapy indicators (274, 278, 279). …”
Section: β2m In Non-renal Diseasesmentioning
confidence: 97%